A Lefebvrian analysis of Airbnb space - Farmaki, Anna; Christou, Prokopis A.; Saveriades, Alexis (My University, 2020)
This paper draws from Lefebvre's spatial triad theory in examining Airbnb space, contributing to knowledge on how space discourses are constructed and in turn internalised in host and guest practices. The study identifies tensions in host-guest-platform relations, illustrating attempts to professionalise and standardise hospitality practices. We conceptualise Airbnb as a space of multiple meanings that reflects the transitionary nature of contemporary hospitality wherein notions, roles and practices are redefined. Conclusively, this paper advocates further research on hospitality's spatial dimensions to uncover the perplexed relations, inherent inequalities and potential opportunities characterising postmodern tourism.
Keywords: Space; Lefebvre; Airbnb; Host-guest-platform relations; Perceptions